2013
DOI: 10.2215/cjn.04680512
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Open-Label Trial of Vitamin E-Bonded Polysulfone Dialyzer and Erythropoiesis-Stimulating Agent Response

Abstract: the VEESA Study Group Summary Background and objectives A 1-year multicenter prospective randomized controlled study was conducted on the effects of vitamin E-bonded polysulfone dialyzers on erythropoiesis-stimulating agent response in hemodialysis patients.Design, setting, participants, & measurements Major inclusion criteria were use of high-flux polysulfone dialyzers with 50-70 ml/min b 2 -microglobulin clearance over 3 months, transferrin saturation over 20%, same erythropoiesisstimulating agent for over 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 18 publications
4
26
0
Order By: Relevance
“…The effect of vitamin E-coated dialyzer on HB level was assessed in six trials, 8,14,15,21,23,25 this meta-analysis showed a nonsignificant increase in HB level compared with that of control (MD, À0.03; 95% CI, À0.18 to 0.13; p ¼ 0.74; Figure 3), with significant heterogeneity between studies (p ¼ 0.06; I 2 ¼ 50%). Six studies reported the EPO dose as mean and standard deviation, 8,[13][14][15]23,25 the fixed model was performed for meta-analysis.…”
Section: Effects On Renal Anemiamentioning
confidence: 96%
See 4 more Smart Citations
“…The effect of vitamin E-coated dialyzer on HB level was assessed in six trials, 8,14,15,21,23,25 this meta-analysis showed a nonsignificant increase in HB level compared with that of control (MD, À0.03; 95% CI, À0.18 to 0.13; p ¼ 0.74; Figure 3), with significant heterogeneity between studies (p ¼ 0.06; I 2 ¼ 50%). Six studies reported the EPO dose as mean and standard deviation, 8,[13][14][15]23,25 the fixed model was performed for meta-analysis.…”
Section: Effects On Renal Anemiamentioning
confidence: 96%
“…Among them, duplicate records, non-RCTs or quasi-RCTs, review and letter, article not in English, other intervention and concerning other outcome were excluded. After the progressive selection process, 14 eligibility studies 1,8,[13][14][15][16][21][22][23][24][25][26][27][28] including five crossover and nine parallel-arm trials were included in this meta-analysis ( Figure 1). …”
Section: Selection and Identification Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations